2010
DOI: 10.1002/bdrc.20177
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage and repair in teratogenesis and neurodevelopmental deficits

Abstract: Several teratogenic agents, including ionizing radiation and xenobiotics such as phenytoin, benzo [a]pyrene, thalidomide, and methamphetamine, can initiate the formation of reactive oxygen species (ROS) that oxidatively damage cellular macromolecules including DNA. Oxidative DNA damage, and particularly the most prevalent 8-oxoguanine lesion, may adversely affect development, likely via alterations in gene transcription rather than via a mutational mechanism. Contributions from oxidative DNA damage do not excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 19 publications
2
54
0
1
Order By: Relevance
“…Even at low levels long term exposure to some PAHs viz., pyrene and BaP has been identified as the cause of cancer in laboratory animals (Diggs et al, 2011). Toxic kinetics study on animal has also shown adverse reproductive and developmental effects from PAHs exposure as such effects have not usually been detected in humans (Wells et al, 2010).…”
Section: Acute or Short-term Health Effects:-mentioning
confidence: 99%
“…Even at low levels long term exposure to some PAHs viz., pyrene and BaP has been identified as the cause of cancer in laboratory animals (Diggs et al, 2011). Toxic kinetics study on animal has also shown adverse reproductive and developmental effects from PAHs exposure as such effects have not usually been detected in humans (Wells et al, 2010).…”
Section: Acute or Short-term Health Effects:-mentioning
confidence: 99%
“…In this section, some similarities between genotoxic effects seen in mES cells and mouse embryos are highlighted, for an extensive review of all effects caused by genotoxicants in mouse embryos I refer to some excellent reviews on the effects of ionizing radiation (De Santis et al 2007) and oxidative stress (Wells et al 2010). …”
Section: Dna Damage In Embryonic Developmentmentioning
confidence: 99%
“…Required ATP is produced through anaerobic respiration. This leads to an accumulation of lactate, acidosis and finally cell death (Wells et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Required ATP is produced through anaerobic respiration. This leads to an accumulation of lactate, acidosis and finally cell death (Wells et al, 2010).The hippocampus, which plays important roles in learning, memory and emotion, is highly vulnerable to ischemic insults. Hypoxia in this region can lead to inhibition of synaptic potential which is a key mechanism to reduce energy consumption (Meilandt et al, 2004).…”
mentioning
confidence: 99%